2005
DOI: 10.1089/sur.2005.6.377
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Activity of Surgical Sutures and Suture- Dependent Bacterial Transport: A Qualitative Study

Abstract: All multifilament and pseudomonofilament suture designs allowed transport of colorants and bacteria to some degree. The movement of fluids and bacteria did not depend on the absorptive capacity of the sutures, coating, or the presence of an open suture end.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 3 publications
0
18
0
3
Order By: Relevance
“…Regrettably, the technique had some disadvantages that threw a shadow of doubts on its success rate in the long-term, because the sample of the study was very small and the amount of lingual mucosa involved in the stitches was smaller than the recorded required minimal amount ( Bademkiran et al., 2006 ; Ducharme et al., 2017 ; Kersjes et al., 1984 ; McCormack, 1976 ; Yong et al., 2008 ), and this may, theoretically, allow the animals to continue suckling themselves after surgery, controversial to the observed short-term high success rate in the study. In addition, the technique associated with excessive swelling of the ventral lingual aspect for few days post- surgery, excessive scar formation, and the stitches buried and may be left permanently in the tongue, that might lower the animal's score in markets, and above all of this, neither the idea of using silk material in a wet environment like oral cavity nor the permanent existence of silk materials in the tongue is acceptable by some specialists of oral surgery ( Silver et al., 2016 ) as leaving such braided multifilament suture material, of high capillary ascension, in tissues for long time, increases the potential risk of bacterial transport through it ( Geiger et al., 2005 ), and predisposes the tongue to glossitis or abscess formation.…”
Section: Discussionmentioning
confidence: 99%
“…Regrettably, the technique had some disadvantages that threw a shadow of doubts on its success rate in the long-term, because the sample of the study was very small and the amount of lingual mucosa involved in the stitches was smaller than the recorded required minimal amount ( Bademkiran et al., 2006 ; Ducharme et al., 2017 ; Kersjes et al., 1984 ; McCormack, 1976 ; Yong et al., 2008 ), and this may, theoretically, allow the animals to continue suckling themselves after surgery, controversial to the observed short-term high success rate in the study. In addition, the technique associated with excessive swelling of the ventral lingual aspect for few days post- surgery, excessive scar formation, and the stitches buried and may be left permanently in the tongue, that might lower the animal's score in markets, and above all of this, neither the idea of using silk material in a wet environment like oral cavity nor the permanent existence of silk materials in the tongue is acceptable by some specialists of oral surgery ( Silver et al., 2016 ) as leaving such braided multifilament suture material, of high capillary ascension, in tissues for long time, increases the potential risk of bacterial transport through it ( Geiger et al., 2005 ), and predisposes the tongue to glossitis or abscess formation.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro and in vivo studies, 12,14 have suggested that VEGF enhances osteoblast differentiation, migration and activity 10 and osteoclast recruitment. 14 So it is able to enhance capillary density 13 playing an important role in angiogenesis associated with osteogenesis. 11,12,15,16 By that, the presence of VEGF fluorescence pattern in FFB grade 0 supports its osteoinductive properties and the increase in VEGF fluorescence pattern after 6 month of graft could be related to the comparison of osteoblasts, osteoclasts, osteocytes and blood vessels, supporting its role in angiogenesis associated with osteogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of foreign material increases the risk of infections [6], especially surgical sutures can act as a wick for SSI [7]. So pathogens from the natural skin flora can easily enter wounds via capillary action.…”
Section: Introductionmentioning
confidence: 99%